Results of primary microbiological screening of modified quercetin derivatives - Osolоdchenko, Tatiana; Andreieva, Iryna; Komisarenko, Mykola; Ryabova, Iryna; Zavada, Nadiya (Annals of Mechnikov's Institute, 2021)
Primary microbiological screening of antimicrobial activity of 315 quercetin derivatives extracted from different plants was performed. For the primary screening standard test cultures of gram-positive and gram-negative bacteria were used that belonged to different taxonomic groups: Staphylococcus aureus ATCC 25923, Esсherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853, Bacillus subtilis ATCC6633, Proteus vulgaris ATCC 4636. Antifungal activity of the compounds was studied for the reference strain of Candida albicans ATCC 885-653. Determination of antimicrobial and anticandidal activity of the new compounds was carried out with the help of the diffusion method of "wells" with the measurement of the diameters of the zones of growth retardation of microorganisms. The moderately sensitive sensitivity of the tested test strains of gram-positive, gram-negative microorganisms and test strain of C. albicans ATCC 653-885 to unmodified, formalized and succylated quercetin of different concentrations was found. Varieties of modified quercetin, additionally modified with the amino acids lysine and arginine, were the most active in terms of antimicrobial action. The vast majority of the studied extracts of quercetin, further modified with amino acids, showed high antimicrobial activity against test strains of gram-positive microorganisms. With regard to gram-negative microorganisms, the most active were succulent extracts of quercetin, modified with amino acids, extracted from the leaves and vines of grapes, raspberry wood, cherry wood, wood and black currant leaves. Moderate anticandidal activity of all investigated samples of quercetin and its modified derivatives was established. The results of the study prove the prospects and feasibility of further in-depth study of the spectrum and degree of antimicrobial activity of selected substances in order to develop new antimicrobial agents based on them. DOI: 10.5281/zenodo.5761159